Behaviour of Rectangular Concrete Filled Tubes and Circular Concrete Filled Tubes under Axial Load - Cintantya Budi Casita; I Putu Ellsa Sarassantika; Roro Sulaksitaningrum (Journal of Applied Sciences, Management and Engineering Technology, 2020)
This paper presents the result behavior of two different type of Concrete Filled Tubes: Rectangular Concrete Filled Tubes (RCFT) and Circular Concrete Filled Tubes (CCFT). In this model, the column end is fixed and the axial load, Paxial, are applied to the column end. The amount of axial load is divided into 5 steps, which increasing continuously. The dimension of the column is 300x300x10 for RCFT and 300x10 for CCFT. As the results, stress distribution, load-deformation curve, load-stress curve, and weight calculation are compared. And it shows that the CCFT gives better performance than the RCFT.